2019
DOI: 10.1002/hipo.23073
|View full text |Cite
|
Sign up to set email alerts
|

Transient hippocampal CA1 lesions in humans impair pattern separation performance

Abstract: Day‐to‐day life involves the perception of events that resemble one another. For the sufficient encoding and retrieval of similar information, the hippocampus provides two essential computational processes. Pattern separation refers to the differentiation of overlapping memory representations, whereas pattern completion reactivates memories based on noisy or degraded input. Evidence from human and rodent studies suggest that pattern separation specifically relies on neuronal ensemble activity in hippocampal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
4
18
1
Order By: Relevance
“…The patients with TGA and lesions on DWI were further examined using fMRI. Similar to the results of previous studies, 12 , 16 , 17 , 20–25 our findings showed that the lesions on DWI were mainly located in the hippocampal CA1 area ( Figure 3 ). Seven of the patients with TGA and hippocampal lesions on DWI were right-handed, suggesting that the left cerebral hemisphere was dominant.…”
Section: Discussionsupporting
confidence: 92%
“…The patients with TGA and lesions on DWI were further examined using fMRI. Similar to the results of previous studies, 12 , 16 , 17 , 20–25 our findings showed that the lesions on DWI were mainly located in the hippocampal CA1 area ( Figure 3 ). Seven of the patients with TGA and hippocampal lesions on DWI were right-handed, suggesting that the left cerebral hemisphere was dominant.…”
Section: Discussionsupporting
confidence: 92%
“…old responses given to the target items minus old responses given to the foils) as a measure of hippocampal integrity (Stark et al, 2013 ), because this index seems to be more sensitive to hippocampal dysfunctions in pathological and normal ageing (Stark et al, 2013 ; Stark, Stevenson, Wu, Rutledge, & Stark, 2015 ) as well as in various psychiatric and neurological disorders (e.g. Hanert, Pedersen, & Bartsch, 2019 ; Kirwan et al, 2012 ). Importantly, although pattern separation is a computational process, lure discrimination reflects behavioral performance on a memory test where for correct discrimination, interference resolution is needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, given our results that STDP impairment did not have a strong negative effect on learning and pattern separation, additional injury mechanisms should be explored in future work. Since damage is known to cause pattern separation deficits in both animals and humans [13,57,58], our results suggest that some additional mechanism beyond STDP impairment must contribute to those effects. Upcoming modeling studies might also examine the interplay between different plasticity algorithms since a stronger homeostatic mechanism might compensate for larger decreases in STDP-related potentiation, thereby preserving baseline untrained activity levels while exposing larger learning deficits.…”
Section: Discussionmentioning
confidence: 75%
“…These trained behaviors depend on discrimination between similar experiences. Recent findings also demonstrate that injury impairs pattern separation in humans [57,58]. The dentate is traditionally the primary focus of studies on hippocampal pattern separation because its intrinsic properties of high inhibition and parallel circuity intuitively support this filter function; however, there is growing evidence that other subregions (CA3 and CA1) also facilitate pattern separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation